Extension of Pairwise Broadcast Clock Synchronization for Multicluster Sensor Networks. (24th January 2008) - Noh Noh, Kyoung-Lae Kyoung-Lae; Wu Wu, Yik-Chung Yik-Chung; Qaraqe Qaraqe, Khalid Khalid; Suter Suter, Bruce W. Bruce W.
Abstract : Time synchronization is crucial for wireless sensor networks (WSNs) in performing a number of fundamental operations such as data coordination, power management, security, and localization. The Pairwise Broadcast Synchronization (PBS) protocol was recently proposed to minimize the number of timing messages required for global network synchronization, which enables the design of highly energy-efficient WSNs. However, PBS requires all nodes in the network to lie within the communication ranges of two leader nodes, a condition which might not be available in some applications. This paper proposes an extension of PBS to the more general class of sensor networks. Based on the hierarchical structure of the network, an energy-efficient pair selection algorithm is proposed to select the best pairwise synchronization sequence to reduce the overall energy consumption. It is shown that in a multicluster networking environment, PBS requires a far less number of timing messages than other well-known synchronization protocols and incurs no loss in synchronization accuracy. Moreover, the proposed scheme presents significant energy savings for densely deployed WSNs.